A novel exidioides fungi, Myxarium boreale (Auriculariales, Basidiomycota) discovered from Northern China - Wang, Xia; Bau, Tolgor (Phytotaxa, 2023)
Myxarium boreale sp. nov., a new species of Myxarium in China, was identified based on ITS and nrLSU sequences along with morphological and molecular phylogenetic analyses. It is characterized by basidiomata gelatinous, cerebriform, hyaline with yellowish-white, with grooves when fresh; they appear as a thin layer that is raw-umber and contains mineral particles on the hymenial surface when dry; when covered with water, they absorb water and expand, slightly transparent, milk-white, and light yellowish is almost invisible; basidia 4(2)-celled, globose to subglobose; basidiospores allantoid to narrow cylindrical; hyphae clamped.